Avaliação dos seios paranasais após osteotomia maxilar tipo LE FORT I - Azevedo, Nayana Oliveira (2018)
The Le Fort I osteotomy is one of the main steps involved in orthognathic surgery, having a relationship with the maxillary sinuses and the nasal cavity. In this way, studies evaluating the correlation of the imaging aspects are added on the actual influence of this surgery on the condition of the paranasal sinuses and anatomical changes of this region. The objective of this study was to evaluate paranasal sinus abnormalities and rhinosinusitis symptomatology in patients submitted to orthognathic surgery using the Le Fort I osteotomy by evaluating tomographic and clinical features. The methodology consisted of the use of concomitant cone beam computed tomography (CBCT) for evaluation of the maxillary sinus volume, detection and diagnosis of anatomical defects. In addition the paranasal sinuses were also classified according to the Lund-Mackay scale. All the aspects evaluated were performed in three times: preoperative (T0), postoperative of up to 30 days (T1) and postoperative of at least 5 months to 01 year (T2). In addition, the Sino-Nasal Outcome 20-item Test (SNOT-20) was used to evaluate the rhinosinusitis symptomatology at the same periods. Statistical analysis was performed using analysis of variance (ANOVA) and Student's t-test for non-paired samples. Among the results obtained, it is noted that the decrease in the air volume of the paranasal sinuses and increase of the values in the scale of Lund-Mackay are present only significantly in T1 in relation to the other two times with p <0.001 in both situations. In addition, the SNOT-20 values decrease significantly when compared to T2 with T1 and T0 with p = 0.0034. Moreover, despite the induction of considerable morphological alterations in T2, these can not be correlated with the results obtained in the other variables. It is concluded that the surgery does not present a risk for the increase of symptoms of rhinosinusitis or tomographic aspects of the sinuses after the follow-up of more than 5 months.